2007
DOI: 10.1097/fjc.0b013e31802ee3d5
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase C and Src Modulate Angiotensin II-Induced Cyclic AMP Production in Preglomerular Microvascular Smooth-Muscle Cells From Spontaneously Hypertensive Rats

Abstract: Our previous study indicates that the phospholipase C family (PLC) and Src kinase family (Src) modulate adrenoceptor-induced cAMP production in a negative and positive manner, respectively, in preglomerular vascular smooth-muscle cells (PGSMCs) obtained from spontaneously hypertensive rats (SHR). Because angiotensin II (Ang II) activates PLC and Src, and because PLC and Src inhibit and augment cAMP production, respectively, it is conceivable that the balance between these signal-transduction pathways determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…We selected isoproterenol as the stimulus because this drug is a β‐adrenoceptor agonist and β‐adrenoceptors are positively coupled to adenylyl cyclase. Moreover, in previous studies, we observed that isoproterenol robustly increased cAMP levels in PGVSMC 24,25 . In the present study, isoproterenol caused a large increase in extracellular levels of cAMP and this increase was strongly suppressed, indeed nearly totally inhibited, by MRP4 siRNA.…”
Section: Discussionsupporting
confidence: 76%
“…We selected isoproterenol as the stimulus because this drug is a β‐adrenoceptor agonist and β‐adrenoceptors are positively coupled to adenylyl cyclase. Moreover, in previous studies, we observed that isoproterenol robustly increased cAMP levels in PGVSMC 24,25 . In the present study, isoproterenol caused a large increase in extracellular levels of cAMP and this increase was strongly suppressed, indeed nearly totally inhibited, by MRP4 siRNA.…”
Section: Discussionsupporting
confidence: 76%
“…Activation of phospholipase C is a key link in numerous metabotropic receptors, including the receptors stimulated in the present study. Inhibition of the function of phospholipase C leads to a reduction in calcium ion concentration in the cytoplasm of cells activated by stimulation of α1-adrenergic receptors (23,24), endothelin type A (25) and angiotensin II receptor type-1 (26).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of PLC is a key event in numerous metabotropic receptors, the physiological response of which was assessed in the present study. Inhibition of PLC function leads to a reduction in the calcium ion concentration in the cytoplasm of cells activated by the stimulation of α1-adrenergic receptors (13,18,19), endothelin receptor type A (20) and angiotensin II receptor type-1 (21). Furthermore, it has been demonstrated that the increase in cytoplasmic calcium concentration induced by PLC is significant at the molecular level and able to induce a significant physiological reponse (14).…”
Section: Discussionmentioning
confidence: 99%